Infection risk in gyms during physical exercise - Andrade, A.; Dominski, F. H.; Pereira, M. L.; de Liz, C. M.; Buonanno, G. (Environmental Science and Pollution Research, 2018)
This study aimed to analyze the risk of infection (influenza and tuberculosis) for individuals participating in physical exercise. This was achieved by assessment of carbon dioxide (CO2) concentrations, and examination of the physical characteristics of a number of gyms to determine whether there was a relationship to CO2 levels. This study was performed in three different gyms ventilated with either split system or central system air conditioners. The risk of airborne infection (percent of susceptible persons infected) was estimated for each gym using the Wells-Riley model. The risk of infection increased during periods of peak occupancy where the ventilation required by occupants was greater. In each gym, the highest risk of infection occurred during the evening where occupancy and CO2 levels were high. The infection risk for influenza was high in all situations due to the high quantum generation rate for this agent. This study suggests that inefficient ventilation in gyms is a significant problem, with high CO2 concentrations resulting in impaired air quality and high health risks to users, including increased risk of infections such as influenza and tuberculosis.